The Impact of Learning Management System on Learning Process in Myanmar: Student Perspective - Htet , Arkar; Liana, Sui Reng; Aung, Theingi; Bhaumik, Amiya (Journal of Engineering Education and Pedagogy, 2023)
The digital transformation of education, accelerated by the Covid-19 pandemic, has spurred widespread adoption of e-learning platforms globally, with Learning Management Systems (LMS) at the forefront. Despite the enhanced communication channels they offer, LMS implementation can introduce unique challenges in the educational arena. This study explores the impact of LMS on the learning process in Myanmar's education system from a student's perspective, focusing on five key factors: convenience, emotional engagement, technological barriers, assessment effectiveness, and cost. A total of 400 questionnaires were distributed to students who had used an LMS, with 264 valid responses received. These were analyzed using SPSS software, revealing significant correlations between all five factors and the learning process, with assessment effectiveness demonstrating the strongest relationship. The results provide valuable insights into how LMS can be optimized to support the learning process in the context of Myanmar's education system, indicating a need for educators and LMS developers to consider these factors for more effective e-learning experiences.